2005
DOI: 10.1039/b203904b
|View full text |Cite
|
Sign up to set email alerts
|

Photoactive metallocyclodextrins: sophisticated supramolecular arrays for the construction of light activated miniature devices

Abstract: The introduction of photoactive metal centres onto cyclodextrin receptors opens up new possibilities for the design of sensors, wires and energy conversion systems. This tutorial review focuses on strategies involving such metallocyclodextrins for the construction of supramolecular arrays with light-activated functions. The assembly procedures for building such arrays are presented, together with the features required for their functions both as sensors for ion or small molecule detection and as wires for phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(46 citation statements)
references
References 37 publications
0
46
0
Order By: Relevance
“…By doing so, it was demonstrated that many chromophore-modified CDs are capable of changing fluorescence and absorption intensities upon inclusion of a guest molecule, and these spectral variations were seen to take place following induced-fit conformational changes of the hosts (Ueno et al, 1990(Ueno et al, , 1992Minato et al, 1991;Kuwabara et al, 1994;Corradini et al, 1996). Other groups have focused on photoactive metal ion-ligand appended CDs, metallocyclodextrins (Haider and Pikramenou, 2005), and applied as chemical sensors. For a very good review on such work please see Ogoshi and Harada (2008).…”
Section: Introductionmentioning
confidence: 97%
“…By doing so, it was demonstrated that many chromophore-modified CDs are capable of changing fluorescence and absorption intensities upon inclusion of a guest molecule, and these spectral variations were seen to take place following induced-fit conformational changes of the hosts (Ueno et al, 1990(Ueno et al, , 1992Minato et al, 1991;Kuwabara et al, 1994;Corradini et al, 1996). Other groups have focused on photoactive metal ion-ligand appended CDs, metallocyclodextrins (Haider and Pikramenou, 2005), and applied as chemical sensors. For a very good review on such work please see Ogoshi and Harada (2008).…”
Section: Introductionmentioning
confidence: 97%
“…Due to their relatively apolar cavities and to their solubilities in water, they can be used in an aqueous solution to interact with apolar molecules, as well as with apolar moieties of amphiphilic molecules, in a variety of different applications [5][6][7]. These characteristics are related to their saccharidic nature, together with the particular spatial disposition of their cyclic chain, with polar groups on the external surface.…”
Section: Introductionmentioning
confidence: 98%
“…[35,36] To date, metallocyclodextrins have generally been used in metal ion sensors, [37,38] small molecule detectors [39] and electron transport wires. [40] However, most of these reports are based on fluorescent phenomena related to the recognition between the cyclodextrin cavity and various guests.…”
Section: Introductionmentioning
confidence: 99%